2019
DOI: 10.3390/ijms20194800
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic Phospholipase A2 Alpha Regulates TLR Signaling and Migration in Metastatic 4T1 Cells

Abstract: Metastatic disease is the leading cause of death in breast cancer patients. Disrupting the cancer cell’s ability to migrate may be a strategy for hindering metastasis. Cytosolic phospholipase A2 α (cPLA2α), along with downstream proinflammatory and promigratory metabolites, has been implicated in several aspects of tumorigenesis, as well as metastasis, in various types of cancer. In this study, we aim to characterize the response to reduced cPLA2α activity in metastatic versus non-metastatic cells. We employ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…Phospholipase can hydrolyze membrane phospholipids to arachidonic acid, which is further involved in many Pathological and physiological processes, including inducing in ammation, transmitting signals, and promoting cell growth, etc. Although one study has shown that down expression of PLA2G4A can promote the migration and invasion of esophageal squamous cell carcinoma [24], most researchers considered that PLA2G4A was an oncogene [25][26][27], which was consistent with our results. The data showed that the expression level of PLA2G4A notably decrease after HULC silencing.…”
Section: Discussionsupporting
confidence: 91%
“…Phospholipase can hydrolyze membrane phospholipids to arachidonic acid, which is further involved in many Pathological and physiological processes, including inducing in ammation, transmitting signals, and promoting cell growth, etc. Although one study has shown that down expression of PLA2G4A can promote the migration and invasion of esophageal squamous cell carcinoma [24], most researchers considered that PLA2G4A was an oncogene [25][26][27], which was consistent with our results. The data showed that the expression level of PLA2G4A notably decrease after HULC silencing.…”
Section: Discussionsupporting
confidence: 91%
“…The cPLA 2 is another intracellular target of C1P, which, upon C1P binding, is activated to release arachidonic acid and thereby increases prostaglandin E 2 (PGE 2 ) formation [32]. Chronic inflammation is a well-known risk factor for cancer development and, in view of our previous findings that the metastatic sublines 4175 and 1833 produce much higher amounts of PGE 2 [26] and that cPLA 2 is implicated in breast cancer cell migration [35,36], it is plausible that the pro-migratory effect of CerK/C1P involves cPLA 2 . However, in our breast cancer model, neither inhibition of CerK with NVP-231 nor CerK knockdown could attenuate PGE 2 formation ( Figure S10), thus excluding the notion that high PGE 2 production in metastatic cells is due to enhanced C1P production by CerK.…”
Section: Discussionmentioning
confidence: 99%
“…Cytosolic phospholipase A 2 (PLA 2 ) degrades membrane phospholipids to generate AA and lysophosphatidic acid [23]. Interestingly, PLA 2 was also reported to be overexpressed in certain cancer cell lines, particularly in the murine breast cancer cell line 4T1 [24] and in basal breast cancer cell lines of human origin such as in MDA-MB-231 and SKBR3 [25][26][27].…”
Section: Introductionmentioning
confidence: 99%